1994
DOI: 10.1126/science.263.5144.221
|View full text |Cite
|
Sign up to set email alerts
|

Root-Knot Nematode—Directed Expression of a Plant Root—Specific Gene

Abstract: Root-knot nematodes are obligate plant parasites that induce development of an elaborate feeding site during root infection. Feeding-site formation results from a complex interaction between the pathogen and the host plant in which the nematode alters patterns of plant gene expression within the cells destined to become the feeding site. Expression of TobRB7, a gene expressed only in tobacco roots, is induced during feeding site development. The cis-acting sequences that mediate induction by the nematode are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
2
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(95 citation statements)
references
References 11 publications
3
88
2
2
Order By: Relevance
“…From our own experiments and those reported by others (Opperman et al, 1994;Chaumont et al, 2000) it should be concluded, however, that plant MIPs expressed in Xenopus oocytes have shown no permeability for any of a great diversity of solutes including sugars, amino acids and ions. The transport of glycerol by certain plant MIPs seems now very well documented (see above), and transport of urea by a TIP4 member (Gerbeau et al, 1999) and of boric acid by a PIP1 homologue (Dordas et al, 2000) has been reported.…”
Section: Solute Transport By Plant Mips?supporting
confidence: 57%
“…From our own experiments and those reported by others (Opperman et al, 1994;Chaumont et al, 2000) it should be concluded, however, that plant MIPs expressed in Xenopus oocytes have shown no permeability for any of a great diversity of solutes including sugars, amino acids and ions. The transport of glycerol by certain plant MIPs seems now very well documented (see above), and transport of urea by a TIP4 member (Gerbeau et al, 1999) and of boric acid by a PIP1 homologue (Dordas et al, 2000) has been reported.…”
Section: Solute Transport By Plant Mips?supporting
confidence: 57%
“…Because Mi-mediated resistance is effected within a narrow time window after RKN invasion (Dropkin, 1969), this result was not surprising. We also found no differences in gene expression (Hutangura et al, 1999;Bird and Koltai, 2000); 3, pathogenesis-related genes (Bowles, 1990); 4, transport (Hammes et al, 2005); 5, nucleic acid binding; 6, (I) shikimate (Doyle and Lambert, 2002); 7, (Y) cell cycle (Niebel et al, 1996;de Almeida Engler et al, 1999); 8, aquaporin, water channel-related genes (Opperman et al, 1994); 9, (X) peroxidase; 10, cell wall (Bird,1974); 11, GC genes ; 12, (S) ribosome-related genes; and 13, genes with unknown function. Annotations were searched with keywords (Supplemental Table S2) to identify genes to categorize.…”
Section: The Root Transcriptome At Rkn Egg Layingmentioning
confidence: 91%
“…Included in this list are genes previously reported to be regulated during RKN pathogenesis, including Aquaporin (Opperman et al, 1994) and ''transport'' (Hammes et al, 2005) genes. We also examined the response of genes encoding host biochemical pathways that have been implicated in the response to RKN.…”
Section: Discussionmentioning
confidence: 99%
“…In addition it was shown that UE treatment up-regulated other defence genes whose induction by marine algal elicitors was not previously reported, notably genes encoding cell wall proteins, calmodulin, ribonuclease, aquaporin and HSR203. Previous reports have indicated that these genes respond to elicitor treatments and/or pathogen attack (Oppermann, Taylor & Conkling 1994;Chappell et al 1997;Galiana et al 1997;Garcia-Muniz, Martinez-Izquierdo & Puigdomenech 1998;Ali et al 2003).…”
Section: Discussionmentioning
confidence: 99%